Pengaruh Tekanan Ketaatan, Kompleksitas Tugas, Pengetahuan, Persepsi Etis Dan Self-Efficacy Terhadap Audit Judgment(Studi empiris pada KAP Surakarta dan Yogyakarta) - Suweknyo, Agung; , Dr. Zulfikar, SE., M.Si (2016)
ABSTRACT Audit judgment is influenced by many factors, both technical and non-technical. One factor technical is the limitation of the scope or timing of the audit, while the non-technical factors such as aspects of individual behavior that is considered to affect audit judgment, namely: gender, pressure obedience, the complexity of the task, experience, knowledge, perception of ethical and self-efficacy, and so on. The results of this study indicate that the variable pressure has a significant level of obedience (0,012) <α (0.05). So that the variable pressure observance effect on audit judgment. the complexity of the task has a significance level of (0.000) <α (0.05). So the task complexity variable effect on audit judgment knowledge variable has a significance level of (0.012) <α (0.05). So the knowledge variable effect on audit judgment. ethical perception variables have a significance level of (0.002) <α (0.05). So the ethical perception variables affect the audit judgment. Self-Efficacy variables have a significance level of (0.005) <α (0.05). Self- Efficacy variables so that the effect on audit judgment. Based on the calculated F value of 9.857 and a significance value of 0.000 with a significant level of 0.05 it can be concluded that, overall, the independent variables include pressure obedience, the complexity of the tasks, knowledge, ethical perception and Self- Efficacy simultaneously affect audit judgment or regression model formed significant for use in the analysis. Keywords: Pressure Obedience. The complexity of the task. Knowledge. Ethical perception. Self-Efficacy. audit Judgment